Highly regioselective C-5 alkynylation of imidazoles by one-pot sequential bromination and Sonogashira cross coupling. Issue 25 (17th June 2015) - Bellina, Fabio; Lessi, Marco; Marianetti, Giulia; Panattoni, Alessandro
Graphical abstract: Abstract: A variety of 2-substituted 5-alkynyl-1 H -imidazoles were easily prepared by a one-pot sequential procedure involving a highly regioselective electrophilic C-5 bromination of 1, 2-dimethyl-1 H -imidazole, 2-chloro-1-methyl-1 H -imidazole, and 2-aryl-1-methyl-1 H- imidazoles, followed by an efficient palladium/copper co-catalyzed Sonogashira-type alkynylation.